(untitled) (Revista Española de Fisiología, 1976)
A double antibody technique of electroimmunodiffusion, which uses glucose oxidase-labelled sheep antibodies to rabbit immunoglobulins as second antibody, is described. Primary antigen-antibody reaction is carried out with a rabbit antiserum by electroimmundiffusion. The glucose oxidase-labelled immunoreagent, being of general application, can serve for the quantification of different antigens and is here used for measurement of low levels of human alpha-fetoprotein. Reproducible results in the range of 50-800 ng/ml were obtained with a variation coefficient of 5 to 10%.